Laparoscopic-assisted versus complete transanal pull-through using Swenson technique in treatment of Hirschsprung's disease - Tamer Fakhry; Ahmed Rabee; Magdy Lolah; Ahmed Nabil (SpringerOpen, 2023)
Abstract Background The aim of this study is to compare outcomes for neonates and infants with Hirschsprung's disease undergoing a laparoscopically assisted transanal pull-through (LAPT) with those undergoing a complete transanal pull-through (TERPT) using Swenson procedure in both groups. Method Forty patients with Hirschsprung's disease were operated between January 2018 and January 2022. Twenty patients underwent transanal endorectal pull through TERPT while the other 20 patients underwent laparoscopic assisted pull through (LAPT) using Swenson procedure (TERPT) in both groups. Age at operation, presenting symptoms, operative time complications, and degree of continence were evaluated. Bowel functions were assessed using the Cleveland Clinic Incontinence Score. Results The mean age of the patients at the time of operation were 18.9 months for the transanal group versus 21.3 months for the laparoscopic group. The mean follow-up period was 6 months, ranging from 3 to 12 months. The rate of enterocolitis occurred in 15% of cases in transanal group versus 10% of cases in the laparoscopic group. Constipation was found in 25% of cases of TERPT group versus 10% of cases in the LAPT group. The rates of normal continence (score 0:4) was 60% vs 50% for TERPT vs LAPT respectively while the rate of severe incontinence (score 15:20) was 20% vs 5% for TERPT vs LAPT respectively. Conclusion The functional outcomes after LAPT was satisfactory in term of fecal soiling compared to trans anal approach this may be due to less pelvic dissection compared to transanal pull through.